ANALISIS KANDUNGAN INFORMASI EKONOMI PENGUMUMAN DAFTAR EFEK SYARIAH (DES) DI INDONESIA - Prasetya, Victor (JAB (Jurnal Akuntansi & Bisnis), 2016)
Research aimed at analyzing and explaining whether or not there are economic information content on the announcement list of effects of Sharia (DES) by the financial services authority (OJK). The content of the information economy defined as positive investor response against Sharia stocks that fall into the DES. Marked by a change in stocks (abnormal return) before and after (surrounding) date announcement DES. In detail the purpose of the research is to find out: (1) developments (in and out) stock in the list of effects. (2) whether or not there is a change in the price of the stock (abnormal return) around the date of the announcement of the list of Shariah-compliant Effects, (3) whether there is influence of the announcement Lists the effects of stock price against Sharia (abnormal return).The testing techniques, among others, the study of events (event study), test the difference t-test with a sample related (related samples) and linear regression Hypothesis test results (test difference t-test and the linear regression test) generally support the research hypothesis, which States there is a change in the price of the stock around the date of the announcement of the list of effects of Sharia (DES) and the announcement of DES to return stock . However, the rate of variation of the variable in explaining DES announcements return stock only amounted to 2.4. This means most of the existence of other factors explained the stock return. The results of the research in General to conclude the existence of a positive response from investors toward stocks Sharia in Indonesia. It is characterized by changes in the stock return (average abnormal return komulatif) before and after (surrounding) date announcement DES. This means also that the publication information content has value DES economies.Â Keywords : A List Of The Effects Of Sharia (DES), Abnormal Return, The Content Of The Information Economy.